Probing molecular interactions of amylose-morin complex and their effect on antioxidant capacity by 2D solid-state NMR spectroscopy. (30th July 2023) - Ma, Yunxiang; Chen, Zidi; Chen, Ruixi; Wang, Zhipeng; Zhang, Shenggui; Chen, Jinfeng
Graphical abstract: Highlights: Molecular interaction of morin and amylose is detected by solid-state NMR. Inter-molecular hydrogen bonds are confirmed by 2D 1 H– 13 C HETCOR spectra. Hydroxy groups are the mainly binding sites of hydrogen bonds. Hydrogen bonds are not strong enough to interfere antioxidant capacity of morin. Abstract: Interaction of polyphenols and starch significantly governed the further applications on polyphenol-starchy foods. Elucidation of inter-molecular interaction is, however, a challenge because conventional characterizations could not detect the change of micro-environment caused by weak interactions. Herein, a facile strategy for molecular detection of amylose-polyphenol interactions was reported using two-dimensional solid-state NMR spectroscopy. Amylose-morin complex was prepared and characterized using 1 H NMR, FT-IR, DSC, XRD and SEM. Significantly, variation of chemical shifts, splitted peaks and peak width, monitored by 13 C CP/MAS and 1 H NMR spectra, identified the strong inter-molecular interaction and binding sites. Furthermore, correlated signals from 1 H– 13 C HETCOR confirmed the binding sites of interactions. These findings confirmed the interaction was inter-molecular hydrogen bonds, which generated between hydroxy-3, 5, 7 of morin and hydroxy groups of amylose. Besides, DPPH radical scavenging and reducing power assay indicated inter-molecular hydrogen bonds are not strong enough to interfere antioxidant capacity of morin.